1993
DOI: 10.1016/0928-8244(93)90008-r
|View full text |Cite
|
Sign up to set email alerts
|

Immunological activity of lipopolysaccharide of Helicobacter pylori on human peripheral mononuclear blood cells in comparison to lipopolysaccharides of other intestinal bacteria

Abstract: Lipopolysaccharide of Helicobacter pylori was tested for its mitogenicity and for its ability to stimulate cytokine release in human peripheral blood mononuclear cells (PBMC) of healthy and H. pylori-infected blood donors. Mitogenicity in PBMC induced by H. pylori LPS was similar to that induced by Campylobacter jejuni lipopolysaccharide, but lower than that induced by Escherichia coli lipopolysaccharide in the H. pylori negative blood donor group. Furthermore, H. pylori LPS was able to induce tumour necrosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
55
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 25 publications
7
55
0
1
Order By: Relevance
“…H. pylori LPS is able to induce toxic lethality in animal models 62 and the secretion of cytokines by human monocytes. 63,64 However, this induction is weaker than that of other tested bacterial LPS. This lower immunological activity of H. pylori LPS is probably a result of its unusual acylation and phosphorylation pattern of lipid A.…”
Section: Relevance Of Strain Types Of H Pylori In the Outcome Of Infmentioning
confidence: 88%
See 1 more Smart Citation
“…H. pylori LPS is able to induce toxic lethality in animal models 62 and the secretion of cytokines by human monocytes. 63,64 However, this induction is weaker than that of other tested bacterial LPS. This lower immunological activity of H. pylori LPS is probably a result of its unusual acylation and phosphorylation pattern of lipid A.…”
Section: Relevance Of Strain Types Of H Pylori In the Outcome Of Infmentioning
confidence: 88%
“…This lower immunological activity of H. pylori LPS is probably a result of its unusual acylation and phosphorylation pattern of lipid A. 63 H. pylori LPS may have an important role in autoimmune-mediated damage in the gastric mucosa. The structure of the LPS O-specific chain in different H. pylori strains may mimic Lewis blood group antigens in structure.…”
Section: Relevance Of Strain Types Of H Pylori In the Outcome Of Infmentioning
confidence: 99%
“…Because endotoxic activity of H. pylori LPS is much lower than LPS from the other enterobacteria (4,26,30), H. pylori LPS is not generally considered as a crucial virulence. On the other hand, guinea pig gastric pit cells, chief cells (46), and enterochromaffin-like cells (20) are highly responsive to H. pylori LPS.…”
Section: Discussionmentioning
confidence: 99%
“…The chemical structure of H. pylori LPS is different from those of other enterobacterial LPSs (5,9,25), and its endotoxic properties are very low compared with other enterobacterial preparations (4,26,30). On the other hand, it was reported that H. felis caused severe atrophic gastritis in C3H/He mice, whereas C3H/HeJ mice with a mutated Toll-like receptor 4 (TLR4) gene showed heavy colonization but minimal atrophic gastritis with much less macrophage infiltration (34).…”
mentioning
confidence: 99%
“…Відомо, що ліпополісахариди, які є головними компонентами зовнішньої мембрани аеробних грам-негативних бактерій E. coli (ендотоксини), у 1000 разів сильніше впливають на виділення про-запальних цитокінів, ніж ліпополісахариди H. pylori [13]. Експериментальні дослідження також показа-ли, що бактеріальні ліпополісахариди порушують процеси гоєння в слизовій оболонці шлунка через зменшення кровотоку в слизовій оболонці шлунка, збільшену експресію та вивільнення про-запальних цитокінів ІЛ-1β та ФНП-α, дисбаланс між про-та анти-апоптичними членами родини Bcl-2 [15].…”
unclassified